How Computers Entered the Classroom: 1960-2000 : Historical Perspectives - Flury, Carmen; Geiss, Michael (Studies in the History of Education and Culture / Studien zur Bildungs- und Kulturgeschichte, 2023)
In the history of education, the question of how computers were introduced into European classrooms has so far been largely neglected. This edited volume strives to address this gap. The contributions shed light on the computerization of general education from a historical perspective, by looking closely at the different actors, political rationales and ideologies, as well as financial, political, or organizational structures and relations.